2021
DOI: 10.1371/journal.pone.0247837
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of DNA repair genes in invasive ductal and lobular breast carcinomas: Insights on individual variations and precision medicine

Abstract: In the era of precision medicine, analyzing the transcriptomic profile of patients is essential to tailor the appropriate therapy. In this study, we explored transcriptional differences between two invasive breast cancer subtypes; infiltrating ductal carcinoma (IDC) and lobular carcinoma (LC) using RNA-Seq data deposited in the TCGA-BRCA project. We revealed 3854 differentially expressed genes between normal ductal tissues and IDC. In addition, IDC to LC comparison resulted in 663 differentially expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…As previously mentioned, hyperglycemia is suggested to have a profound impact on cancer progression. We have also previously observed an upregulation in 36 DDR genes in ductal and lobular breast carcinomas in comparison to normal breast cells [70]. Therefore, we expected that the increase in the expression levels of DDR genes would be specific to the breast cancer cell line (MDA-MB-231).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As previously mentioned, hyperglycemia is suggested to have a profound impact on cancer progression. We have also previously observed an upregulation in 36 DDR genes in ductal and lobular breast carcinomas in comparison to normal breast cells [70]. Therefore, we expected that the increase in the expression levels of DDR genes would be specific to the breast cancer cell line (MDA-MB-231).…”
Section: Discussionmentioning
confidence: 84%
“…In addition, increasing the number of clones analyzed in the microarray analysis would produce better results. Performing RNA-Sequencing could even produce more solid results [70]. However, overall, both the bioinformatics analysis and the wet lab data greatly support an elevation in DDR genes in the presence of high glucose.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies reported the overexpression of some of the genes. This could be owed to biological differences between the patients' samples analyzed in this study and previous studies [71]. Analysis of cell lines versus a cohort of patients can also result in output variability [72].…”
Section: Plos Onementioning
confidence: 83%
“…(2022) found that increased CGA expression was significantly associated with a poor prognosis in patients with breast cancer. H2BC4 was overexpressed in breast cancer (Mohamed et al ., 2021). MSI1 was a negative prognostic indicator of breast cancer patient survival, and was indicative of tumor cells with stem cell-like characteristics (Wang et al ., 2010).…”
Section: Disease Gene Discoverymentioning
confidence: 99%